Boosting the Rate Performance and Capacity of Sb2S3 Nanorods Cathode by Carbon Coating in All‐Solid‐State Lithium Batteries. (20th July 2022) - Ye, Hongjun; Wang, Zaifa; Yan, Jitong; Wang, Zhenyu; Chen, Jingzhao; Dai, Qiushi; Su, Yong; Guo, Baiyu; Li, Hui; Geng, Lin; Du, Congcong; Wang, Jing; et al.
Abstract: Antimony sulfide (Sb2 S3 ) is a promising electrode material. However, its poor electronic/ionic conductivity severely hinders its practical application. Herein, carbon‐coated Sb2 S3 nanorods (Sb2 S3 @C) are synthesized to address this issue. The electrochemical performance of the Sb2 S3 @C is evaluated in all‐solid‐state lithium batteries (ASSLBs) using InLi anode and Li10 Si0.3 PS6.7 Cl1.8 solid‐state electrolytes. The Sb2 S3 @C cathode delivers the 1st cycle discharge capacity of 711 mAh g ‐1 and a stable cycling capacity of 431 mAh g ‐1, which are much higher than the 1st cycle discharge capacity of 125 mAh g ‐1 and a stable cycling capacity of 320 mAh g ‐1 for the uncoated Sb2 S3 cathode. In situ transmission electron microscopy reveals that the carbon coating layer acts as an electronic/ionic conductive conduit, which boosts the charge transfer in the electrode dramatically. Consequently, the Sb2 S3 @C electrochemistry quickly evolves from intercalation to conversion to full alloying. However, the Sb2 S3 nanorods without carbon coating undergo sluggish intercalation and conversion reactions, and the alloying reaction is almost impeded, severely limiting the capacity. Therefore, the Sb2 S3 @C electrode is fully utilized thus delivering much higher capacity and rate performance than the non‐coated Sb2 S3 electrode. These results demonstrate that Sb2 S3 @C is a promising high‐energy‐density cathode for ASSLBs. Abstract : Carbon coating dramatically improves the cyclability of Sb2 S3 cathode in an InLi/LSPSCl/Sb2 S3 @C‐LSPSCl‐C all‐solid‐state lithium battery. A nanobattery is assembled in an environmental transmission electron microscope with Sb2 S3 @C cathode, Li anode, and Li2 O electrolyte to further verify the effect of carbon coated to the lithiation and delithiation reaction kinetics and mechanisms.